Display device substrate and method for producing the same, and antireflection layer resin composition solution used therein

By setting the surface roughness of the surface roughness on the transparent substrates of the LCD display and other display devices, the anti -refractive layer of the surface roughness of 40nm ~ 200Nm and the shading film of the shading layer solves the problem of poorly reflected the surface light reflection of the glu membrane in the existing technology, and achieves lower it. Reflectance and higher contrast.

CN111323951BActive Publication Date: 2025-01-21NIPPON STEEL CHEM & MATERIAL CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN201911259639.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-12-14
Filing Date
2019-12-10
Publication Date
2025-01-21
Estimated Expiration
2039-12-10

AI Technical Summary

Technical Problem

The prior art has poor effect in suppressing light reflection on the surface of the light-shielding film in a display device such as a liquid crystal display, resulting in a problem that surrounding objects are reflected into the picture.

Method used

Set on the transparent substrate, which includes a shading membrane of the anti -reflective layer and the shading layer. The surface roughness of the anti -fire layer is in the range of 40nm to 200nm to further suppress the reflection of the light.

Benefits of technology

It effectively reduces the light reflectivity on the surface of the light-shielding film, reduces the problem of surrounding objects being reflected in the screen, and improves the contrast and anti-light leakage effect of the display device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0002311256060000271
    Figure BDA0002311256060000271
Patent Text Reader

Abstract

The present invention provides a substrate for a display device having a light-shielding film in which light reflection is fully suppressed, a method for manufacturing the same, and a resin composition solution for an anti-reflection layer used therein. The substrate for a display device comprises a transparent substrate and a light-shielding film, wherein the light-shielding film comprises: an anti-reflection layer disposed on the transparent substrate, containing an inorganic filler having a refractive index of 1.2 to 1.8 and a transparent resin hardened material, and having an average thickness of 0.01 μm to 1 μm; and a light-shielding layer disposed on the anti-reflection layer, containing at least one light-shielding component selected from the group consisting of an organic black pigment, an inorganic black pigment, and a mixed color pseudo black pigment, and a resin hardened material, and having an average thickness of 0.1 μm to 30 μm, wherein the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer is 40 nm to 200 nm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a display device substrate and a method for producing the same, and a resin composition solution for an antireflection layer used therein, and more particularly to a display device substrate having a light-shielding film and a method for producing the same, and a resin composition solution for an antireflection layer used therein. Background Art

[0002] In a display device such as a liquid crystal display, a black matrix or other light-shielding film is formed at the boundary of each pixel such as red, green, and blue in a grid, stripe, or mosaic shape for the purpose of improving contrast or preventing light leakage. As such a light-shielding film, a light-shielding film formed on a transparent substrate using a photosensitive resin composition containing a light-shielding component such as a black pigment is known, but in a display device having a transparent substrate with such a light-shielding film disposed on the surface, light incident from the transparent substrate side is reflected on the surface of the light-shielding film (interface with the transparent substrate), so there is a problem that objects placed around are reflected in the screen.

[0003] Therefore, in order to solve such problems as reflection, a method of suppressing the reflection of light on the surface of a shading film has been studied. For example, it is described in International Publication No. 2010 / 070929 (Patent Document 1) that in a display panel substrate having a transparent substrate and a shading layer, two shading layers with different optical concentrations as shading layers are provided on the transparent substrate, and a shading layer with a lower optical concentration than the shading layer with a high optical concentration is arranged between the transparent substrate and the shading layer with a high optical concentration, so as to suppress the reflection of light on the surface of the shading layer. Moreover, it is described in International Publication No. 2014 / 178149 (Patent Document 2) that in a display device substrate having a transparent substrate and a black matrix, a reflectivity-reducing layer and a shading layer whose effective optical concentration as a black matrix is ​​within a specific range are stacked on the transparent substrate to suppress the reflection of light on the surface of the black matrix.

[0004] [Prior art literature]

[0005] [Patent Document]

[0006] [Patent Document 1] International Publication No. 2010 / 070929

[0007] [Patent Document 2] International Publication No. 2014 / 178149 Summary of the invention

[0008] [Problems to be solved by the invention]

[0009] However, in the display device substrates described in Patent Documents 1 and 2, it is not necessarily possible to fully suppress the reflection of light on the surface of the shading film (shading layer, black matrix), and in order to improve contrast or prevent light leakage, it is necessary to further suppress the reflection of light on the shading film.

[0010] The present invention has been made in view of the problems of the conventional technology, and an object of the present invention is to provide a substrate for a display device having a light-shielding film in which reflection of light is sufficiently suppressed, and a method for manufacturing the same.

[0011] [Technical means to solve the problem]

[0012] The inventors of the present invention have repeatedly conducted active research to achieve the above-mentioned purpose, and as a result, have found that in a substrate for a display device having a transparent substrate and a light-shielding film, by providing a light-shielding film including an anti-reflection layer and a light-shielding layer on the transparent substrate, and the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer is within a specific range, the reflection of light on the surface of the light-shielding film can be further suppressed, thereby completing the present invention.

[0013] That is, the substrate for a display device of the present invention includes a transparent substrate and a light-shielding film, wherein the light-shielding film includes: an anti-reflection layer disposed on the transparent substrate, containing an inorganic filler with a refractive index of 1.2 to 1.8 and a transparent resin hardener, and having an average thickness of 0.01 μm to 1 μm; and a light-shielding layer disposed on the anti-reflection layer, containing at least one light-shielding component selected from the group consisting of an organic black pigment, an inorganic black pigment, and a mixed-color pseudo-black pigment, and a resin hardener, and having an average thickness of 0.1 μm to 30 μm, and the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer is 40 nm to 200 nm.

[0014] In such a display device substrate, the inorganic filler preferably has an average particle size of 25 nm to 300 nm, and the content of the inorganic filler is preferably 5 mass % to 95 mass % based on the entire antireflection layer.

[0015] Furthermore, the first method for manufacturing a display device substrate of the present invention is a method for manufacturing a display device substrate including a transparent substrate and a light shielding film including an antireflection layer and a light shielding layer disposed on the transparent substrate, comprising:

[0016] A step of forming a resin composition layer for an antireflection layer on the transparent substrate, which contains an inorganic filler with a refractive index of 1.2 to 1.8 and a photocurable transparent resin, has an average thickness of 0.01 μm to 1 μm and a surface roughness of 40 nm to 200 nm;

[0017] A step of forming a light-shielding layer resin composition layer containing at least one light-shielding component selected from the group consisting of an organic black pigment, an inorganic black pigment, and a mixed color pseudo black pigment and a photocurable resin on the anti-reflection layer resin composition layer; and

[0018] The step of performing exposure treatment on the resin composition layer for the antireflection layer and the resin composition layer for the light-shielding layer, performing development treatment on the layer, and performing heat treatment (post-baking) to form an antireflection layer containing the inorganic filler and the transparent resin cured product and a light-shielding layer containing the light-shielding component and the resin cured product and having an average thickness of 0.1 μm to 30 μm.

[0019] In the first method for producing a display device substrate, preferably, the photocurable transparent resin in the antireflection layer resin composition layer and the photocurable resin in the light shielding layer resin composition layer are both alkali-soluble, and the development treatment is an alkali development treatment.

[0020] Furthermore, a second method for manufacturing a display device substrate of the present invention is a method for manufacturing a display device substrate including a transparent substrate and a light shielding film including an anti-reflection layer and a light shielding layer disposed on the transparent substrate, comprising:

[0021] A step of heat-curing a resin composition for an anti-reflection layer containing an inorganic filler having a refractive index of 1.2 to 1.8 and at least one of a thermosetting transparent resin and a thermosetting monomer to form an anti-reflection layer having an average thickness of 0.01 μm to 1 μm and a surface roughness of 40 nm to 200 nm on the transparent substrate; and

[0022] On the anti-reflection layer, a light-shielding layer resin composition containing at least one light-shielding component selected from the group consisting of organic black pigment, inorganic black pigment and mixed-color pseudo-black pigment and a photocurable resin is subjected to exposure treatment, development treatment, and heat treatment (post-baking) to form a light-shielding layer with an average thickness of 0.1μm to 30μm.

[0023] In the second method for producing a display device substrate, it is preferred that the photocurable resin in the light-shielding layer resin composition layer is alkali-soluble, and the development treatment is an alkali development treatment.

[0024] Furthermore, the first anti-reflection layer resin composition solution of the present invention is a resin composition solution containing a photocurable resin composition and an organic solvent that can form an anti-reflection layer resin composition layer with an average thickness of 0.01 μm to 1 μm and a surface roughness of 40 nm to 200 nm, wherein the photocurable resin composition contains: 5% to 95% by mass of an inorganic filler having a refractive index of 1.2 to 1.8 and an average particle size of 25 nm to 300 nm and dispersible in the organic solvent relative to the entire resin composition; 1.54% to 95% by mass of a photocurable transparent resin relative to the entire resin composition; 0% to 50% by mass of a photopolymerizable monomer relative to the total amount of the photocurable transparent resin and the photopolymerizable monomer; and 0% to 30% by mass of a photopolymerization initiator relative to 100 parts by mass of the total amount of the photocurable transparent resin and the photopolymerizable monomer, and

[0025] The content of the organic solvent is 80% by mass to 99.9% by mass relative to the total amount of the resin composition for an antireflection layer and the organic solvent.

[0026] The solution viscosity is 1 mPa·sec~4 mPa·sec.

[0027] The second antireflection layer resin composition solution of the present invention is a resin composition solution containing a thermosetting resin composition capable of forming an antireflection layer having an average thickness of 0.01 μm to 1 μm and a surface roughness of 40 nm to 200 nm, and an organic solvent.

[0028] The thermosetting resin composition comprises: 5% to 95% by mass of an inorganic filler having a refractive index of 1.2 to 1.8 and an average particle size of 25 nm to 300 nm and dispersible in the organic solvent relative to the entire resin composition; 3.2% to 94.06% by mass of at least one of a thermosetting transparent resin and a thermosetting monomer relative to the entire resin composition; and 1 part to 25 parts by mass of a thermosetting agent relative to 100 parts by mass of the total amount of the thermosetting transparent resin and the thermosetting monomer, and

[0029] The content of the organic solvent is 80% by mass to 99.9% by mass relative to the total amount of the resin composition for an antireflection layer and the organic solvent.

[0030] The solution viscosity is 1 mPa·sec~4 mPa·sec.

[0031] [Effects of the Invention]

[0032] According to the present invention, it is possible to obtain a display device substrate having a light-shielding film in which reflection of light is sufficiently suppressed. DETAILED DESCRIPTION

[0033] Hereinafter, the present invention will be described in detail in conjunction with preferred embodiments thereof.

[0034] First, the display device substrate of the present invention is described. The display device substrate of the present invention includes a transparent substrate and a light-shielding film, wherein the light-shielding film includes: an anti-reflection layer disposed on the transparent substrate, containing an inorganic filler having a refractive index within a specific range and a transparent resin hardener, and having an average thickness within a specific range; a light-shielding layer disposed on the anti-reflection layer, containing at least one light-shielding component selected from the group consisting of an organic black pigment, a mixed color pseudo black pigment, and an inorganic black pigment, and a resin hardener, and having an average thickness within a specific range, and the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer is within a specific range.

[0035] The transparent substrate used in the present invention is not particularly limited, and examples thereof include: a glass substrate, a transparent resin film (polyethylene terephthalate (PET) film, polyethylene naphthalene (PEN) film, polycarbonate film, polyimide film, etc.) and a known transparent substrate used in a display device.

[0036] The light-shielding film in the present invention includes an anti-reflection layer and a light-shielding layer, and in the display device substrate of the present invention, it constitutes a black matrix of a color filter or a complementary metal oxide semiconductor (CMOS) sensor, a frame (bezel) for a touch screen, a black columnar spacer, a black partition wall (barrier (bank) material), etc. Moreover, this light-shielding film is arranged on the transparent substrate, and more specifically, the anti-reflection layer is arranged on the transparent substrate, and the light-shielding layer is arranged on the anti-reflection layer.

[0037] The anti-reflection layer contains an inorganic filler having a refractive index of 1.2 to 1.8. The inorganic filler having such a refractive index has a refractive index smaller than that of the light-shielding component described later. By using such an inorganic filler having a small refractive index, the reflectivity of the light-shielding film is reduced, and the reflection of light on the light-shielding film is suppressed. The refractive index of such an inorganic filler is preferably 1.3 to 1.6, and more preferably 1.4 to 1.5.

[0038] Examples of inorganic fillers having such a refractive index include silicon dioxide (refractive index: 1.46), magnesium fluoride (refractive index: 1.38), lithium fluoride (refractive index: 1.39), and calcium fluoride (refractive index: 1.40), among which silicon dioxide (refractive index: 1.46) is particularly preferred. In addition, such inorganic fillers (especially silicon dioxide) are preferably manufactured or surface-treated so as to be dispersible in an organic solvent. Examples of such silica manufactured or surface-treated to be dispersible in an organic solvent include fumed silica, colloidal silica, and organo silica sol. For example, silica sold under the trade names of organo silica sol manufactured by Nissan Chemical Co., Ltd., admafine and ADMANANO manufactured by Admatechs Co., Ltd., colloidal silica, organo silica sol, and silica nanopowder manufactured by Fuso Chemical Co., Ltd., and fumed silica manufactured by Aerosil Co., Ltd. that can be dispersed in an organic solvent can be used.

[0039] The average particle size of the inorganic filler is preferably 25 nm to 300 nm, more preferably 30 nm to 260 nm, and particularly preferably 30 nm to 220 nm. If the average particle size of the inorganic filler is less than the lower limit, there is a tendency that the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer is less than the lower limit of the specified range. On the other hand, if it exceeds the upper limit, there is a tendency that the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer exceeds the upper limit of the specified range. In addition, the average particle size of the inorganic filler can be obtained by measuring the particle size distribution using a dynamic light scattering method or the like.

[0040] The content of the inorganic filler is preferably 5% to 95% by mass, more preferably 15% to 90% by mass, and particularly preferably 25% to 85% by mass, relative to the entire anti-reflection layer. If the content of the inorganic filler is less than the lower limit, the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer tends to be less than the lower limit of the specified range, while if the content exceeds the upper limit, the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer tends to exceed the upper limit of the specified range.

[0041] Moreover, the anti-reflection layer contains a transparent resin hardener. Such a transparent resin hardener is not particularly limited, and examples thereof include hardeners of light-curing transparent resins or thermosetting transparent resins or thermosetting monomers described later. The content of the transparent resin hardener is preferably 4% to 95% by mass, more preferably 9% to 85% by mass, and particularly preferably 14% to 75% by mass, relative to the entire anti-reflection layer. If the content of the transparent resin hardener is less than the lower limit, there is a tendency that the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer exceeds the upper limit of the specified range. On the other hand, if the content exceeds the upper limit, there is a tendency that the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer is less than the lower limit of the specified range.

[0042] In the light-shielding film of the present invention, the average thickness of the anti-reflection layer is 0.01 μm to 1 μm. If the average thickness of the anti-reflection layer is less than the lower limit, there is a tendency that the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer exceeds the upper limit of the prescribed range. On the other hand, if it exceeds the upper limit, there is a tendency that the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer is less than the lower limit of the prescribed range. As the average thickness of such an anti-reflection layer, from the viewpoint that the surface roughness of the anti-reflection layer is easy to be within the prescribed range, it is preferably 0.02 μm to 0.5 μm, and more preferably 0.04 μm to 0.3 μm. In addition, the average thickness of the anti-reflection layer can be obtained by measuring the step difference between the surface of the anti-reflection layer and the surface of the transparent substrate using a stylus-type step difference shape measuring device and averaging them.

[0043] The light-shielding layer contains at least one light-shielding component selected from the group consisting of an organic black pigment, an inorganic black pigment, and a mixed-color pseudo-black pigment. Examples of organic black pigments include perylene black, aniline black, cyanine black, lactam black, and the like. Examples of inorganic black pigments include carbon black, chromium oxide, iron oxide, titanium black, and the like. Examples of mixed-color pseudo-black pigments include pigments obtained by mixing two or more pigments of red, blue, green, purple, yellow, cyanine, magenta, and the like and performing pseudo-blackening. These light-shielding components may be used alone or in combination of two or more. Moreover, among these light-shielding components, carbon black is particularly preferred from the viewpoint of good light-shielding properties, surface smoothness, dispersion stability, and compatibility with resins.

[0044] The average particle size of the light-shielding component is preferably 10 nm to 300 nm, more preferably 30 nm to 250 nm, and particularly preferably 50 nm to 220 nm. If the average particle size of the light-shielding component is less than the lower limit, the light-shielding property of the light-shielding layer tends to decrease. On the other hand, if the average particle size exceeds the upper limit, the surface smoothness of the light-shielding layer and the uniformity of the dispersion of the light-shielding component tend to decrease. In addition, the average particle size of the light-shielding component can be obtained by measuring the particle size distribution using a dynamic light scattering method or the like.

[0045] As the content of the light-shielding component, when carbon black is used as the light-shielding component, it is preferably 10% to 65% by mass, more preferably 15% to 60% by mass, and particularly preferably 20% to 55% by mass relative to the entire light-shielding layer. Moreover, when a substance other than carbon black is used as the light-shielding component, it is preferably 10% to 90% by mass, more preferably 20% to 80% by mass, and particularly preferably 30% to 70% by mass relative to the entire light-shielding layer. If the content of the light-shielding component is less than the lower limit, there is a tendency for the light-shielding property of the light-shielding layer to decrease. On the other hand, if the content exceeds the upper limit, there is a tendency for the surface smoothness of the light-shielding layer and the uniformity of the dispersion of the light-shielding component to decrease.

[0046] Moreover, the light-shielding layer contains a cured resin. There is no particular limitation on such a cured resin, and examples thereof include cured photocurable resins described later. As for the content of the cured resin, when carbon black is used as a light-shielding component, it is preferably 34% to 90% by mass, more preferably 39% to 85% by mass, and particularly preferably 44% to 80% by mass relative to the entire light-shielding layer. Moreover, when a substance other than carbon black is used as a light-shielding component, it is preferably 9% to 90% by mass, more preferably 19% to 80% by mass, and particularly preferably 29% to 70% by mass relative to the entire light-shielding layer. If the content of the cured resin is less than the lower limit, there is a tendency for the surface smoothness of the light-shielding layer and the uniformity of the dispersion of the light-shielding component to decrease. On the other hand, if the content exceeds the upper limit, there is a tendency for the light-shielding property of the light-shielding layer to decrease.

[0047] In the light-shielding film of the present invention, the average thickness of the light-shielding layer is 0.1 μm to 30 μm. If the average thickness of the light-shielding layer is less than the lower limit, the light-shielding property of the light-shielding layer will decrease. On the other hand, if it exceeds the upper limit, the time required for alkali development will be prolonged, and productivity will decrease. As the average thickness of such a light-shielding layer, from the perspective of taking into account both light-shielding property and productivity, it is preferably 0.5 μm to 20 μm, and more preferably 1 μm to 10 μm. In addition, the average thickness of the light-shielding layer can be calculated as follows: using a stylus-type step difference shape measuring device to measure the step difference between the surface of the light-shielding film and the surface of the transparent substrate, averaging the steps to calculate the average thickness of the light-shielding film, and subtracting the average thickness of the anti-reflection layer from the average thickness of the light-shielding film.

[0048] Moreover, in the light-shielding film of the present invention, the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer is 40nm to 200nm. If the surface roughness of the anti-reflection layer is less than the lower limit, the reflectivity of the light-shielding film cannot be sufficiently reduced, and the reflection of light on the light-shielding film cannot be sufficiently prevented. On the other hand, if the surface roughness of the anti-reflection layer exceeds the upper limit, it is difficult to make the flatness of the light-shielding film reach the desired level. As for the surface roughness of such an anti-reflection layer, the reflectivity of the light-shielding film becomes low, the reflection of light on the light-shielding film is suppressed, and from the perspective of ensuring the flatness of the light-shielding film, it is preferably 50nm to 180nm, and more preferably 80nm to 160nm.

[0049] Next, a method for manufacturing a display device substrate of the present invention is described. A first method for manufacturing a display device substrate of the present invention is a method for manufacturing a display device substrate including a transparent substrate and a light-shielding film including an anti-reflection layer and a light-shielding layer disposed on the transparent substrate, and comprises:

[0050] A step of forming, on the transparent substrate, a resin composition layer for an antireflection layer containing an inorganic filler having a refractive index within a specific range and a photocurable transparent resin, having an average thickness of 0.01 μm to 1 μm and a surface roughness of 40 nm to 200 nm;

[0051] A step of forming a light-shielding layer resin composition layer containing at least one light-shielding component selected from the group consisting of an organic black pigment, an inorganic black pigment, and a mixed color pseudo black pigment and a photocurable resin on the anti-reflection layer resin composition layer; and

[0052] The step of performing exposure treatment on the resin composition layer for the antireflection layer and the resin composition layer for the light-shielding layer, performing development treatment on the layer, and performing heat treatment (post-baking) to form an antireflection layer containing the inorganic filler and the transparent resin cured product and a light-shielding layer containing the light-shielding component and the resin cured product and having an average thickness of 0.1 μm to 30 μm.

[0053] Furthermore, a second method for manufacturing a display device substrate of the present invention is a method for manufacturing a display device substrate including a transparent substrate and a light shielding film including an antireflection layer and a light shielding layer disposed on the transparent substrate, and comprises:

[0054] A step of heat-curing a resin composition for an antireflection layer containing an inorganic filler having a refractive index within a specific range and at least one of a thermosetting transparent resin and a thermosetting monomer to form an antireflection layer having an average thickness of 0.01 μm to 1 μm and a surface roughness of 40 nm to 200 nm on the transparent substrate; and

[0055] On the anti-reflection layer, a light-shielding layer resin composition containing at least one light-shielding component selected from the group consisting of an organic black pigment, an inorganic black pigment, and a mixed color pseudo black pigment and a photocurable resin is subjected to an exposure treatment, a development treatment, and a heat treatment (post-baking) to form a light-shielding layer with an average thickness of 0.1 μm to 30 μm. In this second method for manufacturing a display device substrate, after forming the light-shielding layer (light-shielding layer pattern), if necessary, the anti-reflection layer of the upper part of the anti-reflection layer where the light-shielding layer is not formed (the part where the upper light-shielding layer resin composition layer is removed during the development treatment) is removed by etching treatment, and the anti-reflection layer is also patterned.

[0056] The transparent substrate, inorganic filler having a refractive index in a specific range, and light-shielding component used in the first and second methods for manufacturing a display device substrate of the present invention are the transparent substrate, inorganic filler, and light-shielding component described in the description of the display device substrate of the present invention.

[0057] The resin composition for antireflection layer used in the method for manufacturing the first display device substrate of the present invention (hereinafter referred to as "the first resin composition for antireflection layer") contains the inorganic filler and the photocurable transparent resin. As the photocurable transparent resin, there is no particular limitation as long as it is a transparent resin that can be cured by light irradiation (for example, ultraviolet (UV) irradiation). From the perspective of excellent developability, it is preferably an alkali-soluble photocurable transparent resin, and from the perspective of excellent photocurability and patterning characteristics, it is preferably an alkali-soluble resin containing a polymerizable unsaturated group described in Japanese Patent Laid-Open No. 2017-72760, that is, an epoxy (meth) acrylate acid adduct obtained by further reacting a reaction product of a compound having two or more epoxy groups (more preferably an epoxy compound obtained by reacting a bisphenol with an epihalohydrin) and (meth) acrylic acid (referring to "acrylic acid and / or methacrylic acid") with a polycarboxylic acid or its anhydride, and particularly preferably an epoxy acrylate acid adduct derived from a bisphenol fluorene compound.

[0058] In the first anti-reflection layer resin composition, the content of the inorganic filler is preferably 5% to 95% by mass, more preferably 15% to 90% by mass, and particularly preferably 25% to 85% by mass, relative to the entire first anti-reflection layer resin composition. Moreover, the content of the photocurable transparent resin is preferably 1.54% to 95% by mass, more preferably 3.46% to 85% by mass, and particularly preferably 5.38% to 75% by mass, relative to the entire first anti-reflection layer resin composition. If the content of the inorganic filler is less than the lower limit (or if the content of the photocurable transparent resin exceeds the upper limit), the surface roughness of the anti-reflection layer at the interface between the formed anti-reflection layer and the light-shielding layer tends to be less than the lower limit of the specified range, while on the other hand, if the content of the inorganic filler exceeds the upper limit (or if the content of the photocurable transparent resin is less than the lower limit), the surface roughness of the anti-reflection layer at the interface between the formed anti-reflection layer and the light-shielding layer tends to exceed the upper limit of the specified range.

[0059] Moreover, a photopolymerizable monomer may also be included in this first anti-reflection layer resin composition. Thus, the sensitivity of the anti-reflection layer during optical processing can be rationalized, or the mechanical properties of the film such as the surface hardness of the formed anti-reflection layer can be rationalized. As such a photopolymerizable monomer, there is no particular limitation, and for example, a photopolymerizable monomer having at least one ethylenically unsaturated bond described in Japanese Patent Gazette No. 2017-72760 (for example, (meth) acrylates having at least one ethylenically unsaturated bond) can be cited. As the content of such a photopolymerizable monomer, it is preferably 0% to 50% by mass, more preferably 0% to 40% by mass, and particularly preferably 0% to 30% by mass, relative to the total amount of the photocurable transparent resin and the photopolymerizable monomer.

[0060] Furthermore, it is preferred that a photopolymerization initiator is included in the first anti-reflection layer resin composition. Such a photopolymerization initiator is not particularly limited, and for example, the photopolymerization initiator described in Japanese Patent Laid-Open No. 2017-72760 can be cited, and among these, an oxime ester polymerization initiator is particularly preferred. The content of such a photopolymerization initiator can be appropriately set according to the photocurability of the first anti-reflection layer resin composition, for example, relative to 100 parts by mass of the total amount of the photocurable resin and the photopolymerizable monomer, preferably 0 parts by mass to 30 parts by mass, and more preferably 0 parts by mass to 25 parts by mass.

[0061] Moreover, when the heat resistance of the transparent substrate is low and the post-development heat treatment (post-baking) is performed at a low temperature such as below 150°C, it is preferred that an azo polymerization initiator be included in the first anti-reflection layer resin composition. As a result, the thermal free radical polymerizability of the first anti-reflection layer resin composition during heating after development (post-baking) is improved. There is no particular limitation on such an azo polymerization initiator, and for example, the azo polymerization initiator described in Japanese Patent Laid-Open No. 2017-181976 can be cited. There is no particular limitation on the content of such an azo polymerization initiator, and it can be appropriately set according to the thermal free radical polymerizability of the first anti-reflection layer resin composition.

[0062] In addition, various additives such as a dispersant, a polymerization initiator other than the photopolymerization initiator and the azo polymerization initiator, a chain transfer agent, a sensitizer, a non-photosensitive resin, a hardener, a hardening accelerator, an antioxidant, a plasticizer, a filler, a coupling agent, a surfactant, and a dye may be formulated into the first anti-reflection layer resin composition as needed.

[0063] Moreover, the first anti-reflection layer resin composition is preferably used in the state of a solution (i.e., in the form of a first anti-reflection layer resin composition solution). Thus, a uniform anti-reflection layer resin composition layer can be formed. As the organic solvent used in this first anti-reflection layer resin composition solution, there is no particular limitation, and for example, the solvents described in Japanese Patent Laid-Open No. 2017-72760 can be cited. Regarding this organic solvent, it is preferably prepared in a manner that the amount of organic solvent is 80% by mass to 99.9% by mass relative to the total amount of the first anti-reflection layer resin composition and the organic solvent, and it is more preferably prepared in a manner that the solution viscosity (B-type or E-type viscometer) of the first anti-reflection layer resin composition solution is 1mPa·sec~4mPa·sec. The preferred range of this solution viscosity varies depending on the coating method, so the preferred range of the amount of the organic solvent also varies depending on the coating method. For example, in the case of spin coating, the amount of the organic solvent is preferably 80% to 85% by mass near the lower limit of the preferred range, and in the case of slit coating, the amount of the organic solvent is preferably 99.0% to 99.9% by mass near the upper limit of the preferred range.

[0064] The first antireflection layer resin composition solution of the present invention has a typical formulation composition of a resin composition solution containing a photocurable resin composition and an organic solvent, and in the resin composition solution,

[0065] The photocurable resin composition comprises: 25% to 85% by mass of silica particles having a refractive index of 1.2 to 1.8 and an average particle size of 30 nm to 220 nm, which are dispersible in the organic solvent, relative to the entire resin composition; and 15% to 75% by mass of epoxy (meth)acrylate acid adduct relative to the entire resin composition, and

[0066] The content of the organic solvent is 80 mass % to 99.9 mass % relative to the total amount of the photocurable resin composition and the organic solvent.

[0067] The solution viscosity is 1 mPa·sec to 4 mPa·sec. In the first antireflection layer resin composition solution, the epoxy (meth)acrylate acid adduct is particularly preferably an epoxy acrylate acid adduct derived from a bisphenol fluorene compound.

[0068] On the other hand, the resin composition for the anti-reflection layer used in the method for manufacturing the second display device substrate of the present invention (hereinafter referred to as the "second anti-reflection layer resin composition") contains the inorganic filler and at least one of the thermosetting transparent resin and the thermosetting monomer. As the thermosetting transparent resin and the thermosetting monomer, there is no particular limitation as long as they are transparent resins and monomers that can be cured by heat treatment, for example, resins having ethylenically unsaturated double bonds or cyclic reactive groups (epoxy compounds, oxetane compounds, etc.) and monomers having ethylenically unsaturated double bonds or cyclic reactive groups described in Japanese Patent Laid-Open No. 2016-161926 can be cited.

[0069] In the second anti-reflection layer resin composition, the content of the inorganic filler is preferably 5% to 95% by mass, more preferably 15% to 90% by mass, and particularly preferably 25% to 85% by mass, relative to the entire second anti-reflection layer resin composition. Furthermore, the content of at least one of the thermosetting transparent resin and the thermosetting monomer is preferably 3.2% to 94.06% by mass, more preferably 7.2% to 84.16% by mass, and particularly preferably 11.2% to 74.26% by mass, relative to the entire second anti-reflection layer resin composition. If the content of the inorganic filler is less than the lower limit (or, if the content of the thermosetting transparent resin exceeds the upper limit), there is a tendency that the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer formed is less than the lower limit of the specified range. On the other hand, if the content of the inorganic filler exceeds the upper limit (or, if the content of the thermosetting transparent resin is less than the lower limit), there is a tendency that the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the light-shielding layer formed is more than the upper limit of the specified range.

[0070] Furthermore, it is preferred that the second antireflection layer resin composition contains a thermosetting agent. As such a thermosetting agent, for example, thermosetting agents for epoxy compounds such as amine compounds, polycarboxylic acid compounds, phenol resins, amino resins, dicyandiamide, and Lewis acid complex compounds can be used, among which polycarboxylic acid compounds are preferred. As such a polycarboxylic acid compound, polycarboxylic acids, polycarboxylic acid anhydrides, and thermally decomposable esters of polycarboxylic acids can be cited. Polycarboxylic acid is a compound having two or more carboxyl groups in one molecule, and specifically includes succinic acid, maleic acid, cyclohexane-1,2-dicarboxylic acid, cyclohexene-1,2-dicarboxylic acid, cyclohexene-4,5-dicarboxylic acid, norbornane-2,3-dicarboxylic acid, phthalic acid, 3,6-dihydrophthalic acid, 1,2,3,6-tetrahydrophthalic acid, methyltetrahydrophthalic acid, benzene-1,2,4-tricarboxylic acid, cyclohexane-1,2,4-tricarboxylic acid, benzene-1,2,4,5-tetracarboxylic acid, cyclohexane-1,2,4,5-tetracarboxylic acid, butane-1,2,3,4-tetracarboxylic acid, etc. As the anhydride of the polycarboxylic acid, the anhydride of the polycarboxylic acid exemplified above can be listed. As the anhydride of such a polycarboxylic acid, an intermolecular anhydride can be used, and generally an anhydride that is ring-closed in the molecule is used. As the thermally decomposable esters of polycarboxylic acids, the thermally decomposable esters of the polycarboxylic acids exemplified above can be listed (e.g., tert-butyl ester, 1-(alkyloxy)ethyl ester, 1-(alkylthio)ethyl ester, etc. [wherein, the alkyl group is a saturated or unsaturated hydrocarbon group having 1 to 20 carbon atoms, and the hydrocarbon group may have any structure of a straight chain, a branched structure, or a cyclic structure, and may also have any substituent). In addition, as the polycarboxylic acid-based compound, a polymer or copolymer having two or more carboxyl groups can also be used, and the carboxyl group can also form an anhydride group or a thermally decomposable ester group. There are no particular restrictions on such polymers or copolymers having two or more carboxyl groups, and examples thereof include polymers or copolymers containing (meth)acrylic acid as a constituent component, copolymers containing maleic anhydride as a constituent component, compounds formed by reacting tetracarboxylic dianhydride with a diamine or a diol to open the anhydride ring, and the like. Among these polycarboxylic acid compounds, anhydrides of polycarboxylic acids such as phthalic acid, 3,6-dihydrophthalic acid, 1,2,3,6-tetrahydrophthalic acid, methyltetrahydrophthalic acid, and benzene-1,2,4-tricarboxylic acid are preferred. The content of such a thermosetting agent can be appropriately set according to the thermosetting properties of the second antireflection layer resin composition, and is preferably 1 to 25 parts by mass relative to 100 parts by mass of the total amount of the thermosetting transparent resin and the thermosetting monomer.

[0071] Furthermore, various additives such as a dispersant, a non-thermosetting resin, a curing accelerator, an antioxidant, a plasticizer, a filler, a coupling agent, a surfactant, and a dye may be formulated into the second antireflection layer resin composition as needed.

[0072] Moreover, the second anti-reflection layer resin composition is preferably used in the state of a solution (i.e., in the form of a second anti-reflection layer resin composition solution). Thus, a uniform anti-reflection layer resin composition layer can be formed. There is no particular limitation on the organic solvent used in this second anti-reflection layer resin composition solution, and for example, the solvents described in Japanese Patent Laid-Open No. 2016-161926 can be cited. Regarding this organic solvent, it is preferably prepared in a manner that the amount of organic solvent is 80% by mass to 99.9% by mass relative to the total amount of the second anti-reflection layer resin composition and the organic solvent, and it is more preferably prepared in a manner that the solution viscosity (B-type or E-type viscometer) of the second anti-reflection layer resin composition solution is 1mPa·sec to 4mPa·sec. The preferred range of this solution viscosity varies depending on the coating method, so the preferred range of the amount of the organic solvent also varies depending on the coating method. For example, in the case of spin coating, the amount of the organic solvent is preferably 80% to 85% by mass near the lower limit of the preferred range, and in the case of slit coating, the amount of the organic solvent is preferably 99.0% to 99.9% by mass near the upper limit of the preferred range.

[0073] The second antireflection layer resin composition solution of the present invention has a typical formulation composition of a resin composition solution containing a thermosetting resin composition and an organic solvent, and in the resin composition solution,

[0074] The thermosetting resin composition comprises: 25% to 85% by mass of silica particles having a refractive index of 1.2 to 1.8 and an average particle size of 30 nm to 220 nm, which are dispersible in the organic solvent, relative to the entire resin composition; 12% to 74.26% by mass of an epoxy compound, relative to the entire resin composition; and 1 part to 25 parts by mass of a thermosetting agent, relative to 100 parts by mass of the epoxy compound, and

[0075] The content of the organic solvent is 80 mass % to 99.9 mass % relative to the total amount of the photocurable resin composition and the organic solvent.

[0076] The solution viscosity is 1 mPa·sec~4 mPa·sec.

[0077] The resin composition for the light-shielding layer used in the manufacturing method of the first and second display device substrates of the present invention contains the light-shielding component and the photocurable resin. As the photocurable resin, as long as it is a resin that can be cured by light irradiation (for example, UV irradiation), there is no particular limitation. From the perspective of excellent developability, it is preferably an alkali-soluble photocurable resin, and from the perspective of excellent photocurability and patterning properties, it is preferably an alkali-soluble resin containing a polymerizable unsaturated group described in Japanese Patent Laid-Open No. 2017-72760, that is, a compound having two or more epoxy groups (more preferably an epoxy compound obtained by reacting bisphenols with epihalohydrins) and (meth) acrylic acid (referring to "acrylic acid and / or methacrylic acid") The reaction product is further reacted with a polycarboxylic acid or its anhydride to obtain an epoxy (meth) acrylate acid adduct, and is particularly preferably an epoxy acrylate acid adduct derived from a bisphenol fluorene compound.

[0078] In such a light-shielding layer resin composition, the content of the light-shielding component is preferably 10% to 90% by mass, more preferably 20% to 80% by mass, and particularly preferably 30% to 70% by mass, relative to the entire light-shielding layer resin composition. Moreover, the content of the photocurable resin is preferably 5.54% to 90% by mass, more preferably 11.7% to 80% by mass, and particularly preferably 17.8% to 70% by mass, relative to the entire light-shielding layer resin composition. If the content of the light-shielding component is less than the lower limit (or the content of the photocurable resin exceeds the upper limit), the light-shielding property of the formed light-shielding layer tends to decrease. On the other hand, if the content of the light-shielding component exceeds the upper limit (or the content of the photocurable resin is less than the lower limit), the surface smoothness of the formed light-shielding layer and the dispersion stability of the light-shielding component tend to decrease.

[0079] Moreover, a photopolymerizable monomer may also be included in this light-shielding layer resin composition. Thus, it is possible to rationalize the sensitivity of the light-shielding layer when performing optical processing, or to rationalize the mechanical properties of the film such as the surface hardness of the formed light-shielding layer. As such a photopolymerizable monomer, a photopolymerizable monomer having at least one ethylenically unsaturated bond described in Japanese Patent Laid-Open No. 2017-72760 (for example, (meth)acrylates having at least one ethylenically unsaturated bond) can be cited. As the content of such a photopolymerizable monomer, it is preferably 1% to 20% by mass, more preferably 2% to 15% by mass, and particularly preferably 3% to 10% by mass, relative to the total amount of the photocurable resin and the photopolymerizable monomer.

[0080] Furthermore, it is preferred that a photopolymerization initiator is included in the light-shielding layer resin composition. Such a photopolymerization initiator is not particularly limited, and for example, the photopolymerization initiator described in Japanese Patent Laid-Open No. 2017-72760 can be cited, and among these, an oxime ester polymerization initiator is particularly preferred. The content of such a photopolymerization initiator can be appropriately set according to the photocurability of the light-shielding layer resin composition, for example, relative to 100 parts by mass of the total amount of the photocurable resin and the photopolymerizable monomer, preferably 0.3 parts by mass to 30 parts by mass, and more preferably 1 part by mass to 25 parts by mass.

[0081] Moreover, when the heat resistance of the transparent substrate is low and the post-development heat treatment (post-baking) is performed at a low temperature such as below 150°C, it is preferred to include an azo polymerization initiator in the light-shielding layer resin composition. As a result, the thermal free radical polymerizability of the light-shielding layer resin composition during heating after development (post-baking) is improved. As such an azo polymerization initiator, there is no particular limitation, and for example, the azo polymerization initiator described in Japanese Patent Laid-Open No. 2017-181976 can be cited. As the content of such an azo polymerization initiator, there is no particular limitation, and it can be appropriately set according to the thermal free radical polymerizability of the light-shielding layer resin composition.

[0082] In addition, in the resin composition for the light-shielding layer, various additives such as a dispersant, a polymerization initiator other than the photopolymerization initiator and the azo polymerization initiator, a chain transfer agent, a sensitizer, a non-photosensitive resin, a hardener, a hardening accelerator, an antioxidant, a plasticizer, a filler, a coupling agent, a surfactant, a pigment for color adjustment, a dye, etc. can be formulated as needed.

[0083] Moreover, the light-shielding layer resin composition is preferably used in the state of a solution (i.e., in the form of a light-shielding layer resin composition solution). Thus, a uniform light-shielding layer resin composition layer can be formed. There is no particular limitation on the organic solvent used in this light-shielding layer resin composition solution, and for example, the solvents described in Japanese Patent Laid-Open No. 2017-72760 can be cited. Regarding this organic solvent, it is preferably prepared in a manner that the amount of the organic solvent becomes 60% to 90% by mass relative to the total amount of the light-shielding layer resin composition and the organic solvent, and it is more preferably prepared in a manner that the solution viscosity (B-type or E-type viscometer) of the light-shielding layer resin composition solution becomes 1mPa·sec to 30mPa·sec.

[0084] In the first method for producing a display device substrate of the present invention, first, a layer comprising the first antireflection layer resin composition (hereinafter referred to as "first antireflection layer resin composition layer") is formed on the transparent substrate.

[0085] The average thickness of the first antireflection layer resin composition layer is 0.01 μm to 1 μm. If the average thickness of the first antireflection layer resin composition layer is less than the lower limit, there is a tendency that the surface roughness of the first antireflection layer resin composition layer exceeds the upper limit of the specified range. On the other hand, if it exceeds the upper limit, there is a tendency that the surface roughness of the first antireflection layer resin composition layer is less than the lower limit of the specified range. As the average thickness of such a first antireflection layer resin composition layer, from the viewpoint that the surface roughness of the first antireflection layer resin composition layer is easily within the specified range, it is preferably 0.02 μm to 0.5 μm, and more preferably 0.04 μm to 0.3 μm. In addition, the average thickness of the first antireflection layer resin composition layer can be obtained by measuring the step difference between the surface of the first antireflection layer resin composition layer and the surface of the transparent substrate using a stylus-type step difference shape measuring device and averaging them.

[0086] Moreover, the surface roughness of the first anti-reflection layer resin composition layer is 40nm to 200nm. If the surface roughness of the first anti-reflection layer resin composition layer is less than the lower limit, the reflectivity of the obtained light-shielding film cannot be sufficiently reduced, and the reflection of light on the light-shielding film cannot be fully prevented. On the other hand, if the surface roughness of the first anti-reflection layer resin composition layer exceeds the upper limit, it is difficult to make the flatness of the obtained light-shielding film reach the desired level. As the surface roughness of such a first anti-reflection layer resin composition layer, the reflectivity of the obtained light-shielding film becomes low, the reflection of light on the light-shielding film is suppressed, and from the perspective of ensuring the flatness of the light-shielding film, it is preferably 50nm to 180nm, and more preferably 80nm to 160nm. In addition, the surface roughness of the resin composition layer for the first anti-reflection layer can be calculated as follows: the concavo-convex shape of the surface of the resin composition layer for the first anti-reflection layer is measured using a stylus-type step shape measuring device to obtain a roughness curve, and the arithmetic mean of the roughness of a 0.1 mm portion randomly extracted from the roughness curve is calculated and used as the surface roughness of the resin composition layer for the first anti-reflection layer.

[0087] As a method for forming such a first antireflection layer resin composition layer, for example, there is a method of applying a solution of the first antireflection layer resin composition on the transparent substrate and then subjecting the coating to a heat treatment (prebaking) to remove the organic solvent.

[0088] Next, a layer including the light-shielding layer resin composition (hereinafter referred to as "light-shielding layer resin composition layer") is formed on the first antireflection layer resin composition layer thus formed. As a method for forming such a light-shielding layer resin composition layer, for example, a method of applying the light-shielding layer resin composition solution on the first antireflection layer resin composition layer and then performing a heat treatment (pre-baking) to remove the organic solvent can be cited.

[0089] As a method for coating the first antireflection layer resin composition solution and a method for coating the light shielding layer resin composition solution, for example, in addition to the known solution dipping method and spraying method, there can also be cited methods using a roll coater, a top coater, a slit coater, a spin coater, etc. The heating temperature and heating time in the pre-baking can be appropriately set according to the type of organic solvent used, for example, the heating temperature can be set to 60°C to 110°C (set to not exceed the heat resistance temperature of the transparent substrate), and the heating time can be set to 1 minute to 3 minutes.

[0090] Next, the first anti-reflection layer resin composition layer and the light-shielding layer resin composition layer thus formed are simultaneously subjected to an exposure treatment using a desired light-shielding film pattern-forming mask, so that the photocurable transparent resin of the photosensitive portion (exposed portion) of the first anti-reflection layer resin composition layer and the photocurable resin of the photosensitive portion (exposed portion) of the light-shielding layer resin composition layer are photocured. The exposure treatment conditions can be appropriately set according to the type of photocurable resin or photopolymerization initiator used.

[0091] Next, the first anti-reflection layer resin composition layer and the light-shielding layer resin composition layer after exposure are subjected to development treatment at the same time, and the resin composition of the unexposed part of the first anti-reflection layer resin composition layer and the light-shielding layer resin composition layer is removed, thereby simultaneously forming an anti-reflection layer containing the inorganic filler and the transparent resin cured product (cured product of the first anti-reflection layer resin composition) and a light-shielding layer containing the light-shielding component and the resin cured product (cured product of the light-shielding layer resin composition). In addition, in order to fully cure the anti-reflection layer and the light-shielding layer, or to fully remove the developer to improve the adhesion between the transparent substrate and the anti-reflection layer, the anti-reflection layer and the light-shielding layer are subjected to heat treatment (post-baking), thereby obtaining a display device substrate of the present invention having a light-shielding film (light-shielding film pattern) including the anti-reflection layer and the light-shielding layer on the transparent substrate.

[0092] There is no particular limitation on the development method, and a known development method can be used. The development conditions can be appropriately set according to the type of photocurable transparent resin and photocurable resin used. In addition, when the photocurable transparent resin in the first anti-reflection layer resin composition layer and the photocurable resin in the light-shielding layer resin composition layer are alkali-soluble, it is preferred to use an alkali developer for development (alkali development). As the alkali developer, a known alkali developer such as an aqueous solution of a carbonate or hydroxide of an alkali metal or alkaline earth metal can be used.

[0093] Moreover, the heating temperature and heating time in the post-bake can be appropriately set according to the type of transparent substrate or resin composition used. For example, when using a glass substrate or other sufficiently heat-resistant substrate as the transparent substrate, the heating temperature can be set to 180°C to 250°C, and the heating time can be set to 20 minutes to 60 minutes.

[0094] The average thickness of the light-shielding layer thus formed is 0.1 μm to 30 μm. If the average thickness of the light-shielding layer is less than the lower limit, the light-shielding property will decrease. On the other hand, if it exceeds the upper limit, the time required for the alkali development will be prolonged, and the productivity will decrease. As the average thickness of such a light-shielding layer, from the perspective of taking into account both light-shielding property and productivity, it is preferably 0.5 μm to 20 μm, and more preferably 1 μm to 10 μm. In addition, the average thickness of the light-shielding layer can be obtained as follows: using a stylus-type step difference shape measuring device to measure the step difference between the surface of the light-shielding layer and the surface of the transparent substrate, averaging the steps to obtain the average thickness of the light-shielding film including the anti-reflection layer and the light-shielding layer, and subtracting the average thickness of the first anti-reflection layer resin composition layer from the average thickness of the light-shielding film.

[0095] Thus, in the manufacturing method of the first display device substrate of the present invention, a photocurable resin is used in either the first antireflection layer resin composition or the light-shielding layer resin composition, so the first antireflection layer resin composition layer and the light-shielding layer resin composition layer can be exposed and developed at the same time.

[0096] On the other hand, in the manufacturing method of the second display device substrate of the present invention, first, on the transparent substrate, the second anti-reflection layer resin composition is subjected to a heat curing treatment to form an anti-reflection layer containing the inorganic filler and a transparent resin cured product (the cured product of the second anti-reflection layer resin composition).

[0097] The average thickness of the anti-reflection layer is 0.01 μm to 1 μm. If the average thickness of the anti-reflection layer is less than the lower limit, there is a tendency that the surface roughness of the anti-reflection layer exceeds the upper limit of the specified range. On the other hand, if it exceeds the upper limit, there is a tendency that the surface roughness of the anti-reflection layer is less than the lower limit of the specified range. As the average thickness of such an anti-reflection layer, from the viewpoint that the surface roughness of the anti-reflection layer is easily within the specified range, it is preferably 0.02 μm to 0.5 μm, and more preferably 0.04 μm to 0.3 μm. In addition, the average thickness of the anti-reflection layer can be obtained by measuring the step difference between the surface of the anti-reflection layer and the surface of the transparent substrate using a stylus-type step difference shape measuring device and averaging them.

[0098] Moreover, the surface roughness of the anti-reflection layer is 40nm to 200nm. If the surface roughness of the anti-reflection layer is less than the lower limit, the reflectivity of the obtained light-shielding film cannot be sufficiently reduced, and the reflection of light on the light-shielding film cannot be sufficiently prevented. On the other hand, if the surface roughness of the anti-reflection layer exceeds the upper limit, it is difficult to make the flatness of the obtained light-shielding film reach the desired level. As for the surface roughness of such an anti-reflection layer, the reflectivity of the obtained light-shielding film is further reduced, the reflection of light on the light-shielding film is further suppressed, and from the perspective of ensuring the flatness of the light-shielding film, it is preferably 50nm to 180nm, and more preferably 80nm to 160nm. In addition, the surface roughness of the anti-reflection layer can be obtained as follows: using a stylus-type step difference shape measuring device to measure the concave-convex shape of the surface of the anti-reflection layer, obtain a roughness curve, and for a 0.1mm portion randomly extracted from the roughness curve, the arithmetic mean of the roughness is obtained, and it is used as the surface roughness of the anti-reflection layer.

[0099] As a method for forming such an antireflection layer, for example, there can be mentioned a method of applying a solution of the second antireflection layer resin composition on the transparent substrate and then subjecting the second antireflection layer resin composition to a heat curing treatment.

[0100] Examples of the method for coating the second antireflection layer resin composition solution include methods using a roll coater, a top coater, a slit coater, a spin coater, and the like, in addition to known solution dipping methods and spraying methods.

[0101] Moreover, the heat curing treatment conditions can be appropriately set according to the type of transparent substrate or the second anti-reflection layer resin composition used. For example, when a glass substrate or other substrate with sufficient heat resistance is used as the transparent substrate, the heating temperature can be set to 180°C to 250°C, and the heating time can be set to 20 minutes to 60 minutes.

[0102] Next, a layer comprising the light-shielding layer resin composition (hereinafter referred to as "light-shielding layer resin composition layer") is formed on the anti-reflection layer thus formed. As a method for forming such a light-shielding layer resin composition layer, for example, a method of applying the light-shielding layer resin composition solution on the second anti-reflection layer resin composition layer and then performing a heat treatment (pre-baking) to remove the organic solvent can be cited.

[0103] As a method for coating the light-shielding layer resin composition solution, for example, in addition to the known solution dipping method and spraying method, there can also be cited methods using a roll coater, a surface coater, a slit coater, a spin coater, etc. The heating temperature and heating time in the pre-baking can be appropriately set according to the type of organic solvent used, for example, the heating temperature can be set to 60°C to 110°C (set to not exceed the heat resistance temperature of the transparent substrate), and the heating time can be set to 1 minute to 3 minutes.

[0104] Next, the light-shielding layer resin composition layer thus formed is subjected to an exposure treatment using a desired light-shielding film pattern-forming mask to photo-cure the photocurable resin in the photosensitive portion (exposed portion) of the light-shielding layer resin composition layer. The exposure treatment conditions can be appropriately set according to the type of photocurable resin or photopolymerization initiator used.

[0105] Next, the light-shielding layer resin composition layer after exposure is subjected to a development treatment to remove the resin composition of the unexposed portion of the light-shielding layer resin composition layer, thereby forming a light-shielding layer containing the light-shielding component and the resin cured product (cured product of the light-shielding layer resin composition). Furthermore, in order to fully cure the light-shielding layer or to fully remove the developer, the light-shielding layer is subjected to a heat treatment (post-baking), thereby obtaining a display device substrate of the present invention having a light-shielding film (light-shielding film pattern) including the anti-reflection layer and the light-shielding layer on the transparent substrate.

[0106] There is no particular limitation on the development method, and a known development method can be used. The development conditions can be appropriately set according to the type of photocurable resin used. In addition, when the photocurable resin in the light-shielding layer resin composition layer is alkali-soluble, it is preferred to use an alkali developer for development (alkali development). As the alkali developer, a known alkali developer such as an aqueous solution of a carbonate or hydroxide of an alkali metal or alkaline earth metal can be used.

[0107] The heating temperature and heating time in the post-bake can be appropriately set according to the type of the transparent substrate or resin composition used.

[0108] The average thickness of the light-shielding layer thus formed is 0.1 μm to 30 μm. If the average thickness of the light-shielding layer is less than the lower limit, the light-shielding property will decrease. On the other hand, if it exceeds the upper limit, the time required for the alkali development will be prolonged, and the productivity will decrease. As the average thickness of such a light-shielding layer, from the perspective of taking into account both light-shielding property and productivity, it is preferably 0.5 μm to 20 μm, and more preferably 1 μm to 10 μm. In addition, the average thickness of the light-shielding layer can be calculated as follows: using a stylus-type step difference shape measuring device to measure the step difference between the surface of the light-shielding layer and the surface of the transparent substrate, averaging the steps to calculate the average thickness of the light-shielding film including the anti-reflection layer and the light-shielding layer, and subtracting the average thickness of the anti-reflection layer from the average thickness of the light-shielding film.

[0109] [Example]

[0110] The present invention is described in more detail below based on the examples and comparative examples, but the present invention is not limited to the following examples. In addition, the average particle size of the inorganic filler and the light-shielding component used in the examples and comparative examples, the average thickness of the anti-reflection layer (or the resin composition layer for the anti-reflection layer) and the light-shielding layer, and the surface roughness of the anti-reflection layer (or the resin composition layer for the anti-reflection layer) are measured by the following method.

[0111] <Measurement of average particle size of inorganic filler and light-shielding component>

[0112] The particles of the inorganic filler or the light-shielding component are dispersed in the organic solvent used in the resin composition solution so that the particle concentration becomes 0.1 mass % to 0.5 mass %. The particle size distribution of the particles in the obtained dispersion is measured by a dynamic light scattering method using a particle size distribution meter ("Particle Size Analyzer FPAR-1000" manufactured by Otsuka Electronics Co., Ltd.), and the obtained particle size distribution is analyzed by a cumulative amount method to obtain the average particle size (average secondary particle size).

[0113] <Measurement of average thickness of antireflection layer (or resin composition layer for antireflection layer)>

[0114] Using a stylus-type step shape measuring device ("P-10" manufactured by KLA-Tencor), the step difference between the surface of the glass substrate and the surface of the anti-reflection layer (or the surface of the resin composition layer for the anti-reflection layer) was measured under the conditions of a measuring range of 500 μm, a scanning speed of 50 μm / second, and a sampling rate of 20 Hz, and the average value was taken as the average thickness of the anti-reflection layer (or the resin composition layer for the anti-reflection layer).

[0115] <Measurement of average thickness of light shielding layer>

[0116] Using a stylus-type step shape measuring device ("P-10" manufactured by KLA-Tencor), the step difference between the surface of the glass substrate and the surface of the light-shielding layer was measured under the conditions of a measuring range of 500 μm, a scanning speed of 50 μm / second, and a sampling rate of 20 Hz, and the average value thereof was taken as the average thickness of the light-shielding film including the anti-reflection layer and the light-shielding layer. The average thickness of the light-shielding layer (or the resin composition layer for the anti-reflection layer) was subtracted from the average thickness of the light-shielding film to obtain the average thickness of the light-shielding layer (= the average thickness of the light-shielding film - the average thickness of the anti-reflection layer (or the resin composition layer for the anti-reflection layer)).

[0117] <Measurement of surface roughness of antireflection layer (or resin composition layer for antireflection layer)>

[0118] The concavoconvex shape of the surface of the anti-reflection layer (or the surface of the resin composition layer for the anti-reflection layer) was measured using a stylus-type step shape measuring device ("P-10" manufactured by KLA-Tencor) under the conditions of a measuring range of 500 μm, a scanning speed of 10 μm / second, and a sampling rate of 100 Hz, and a roughness curve was obtained. The arithmetic mean of the roughness of a portion of 0.1 mm length randomly extracted from the roughness curve was obtained and used as the surface roughness of the anti-reflection layer (or the resin composition layer for the anti-reflection layer). The results are shown in Table 1.

[0119] The alkali-soluble photocurable transparent resin used in the examples and comparative examples was synthesized by the following method. The raw materials used in the synthesis examples are shown below.

[0120] BPFE: bisphenol fluorene type epoxy compound (reaction product of 9,9-bis(4-hydroxyphenyl)fluorene and chloromethyloxirane (epoxide equivalent: 250 g / eq)).

[0121] AA: Acrylic acid.

[0122] PGMEA: propylene glycol monomethyl ether acetate.

[0123] TEAB: tetraethylammonium bromide.

[0124] BPDA: 3,3',4,4'-biphenyltetracarboxylic dianhydride.

[0125] THPA: Tetrahydrophthalic anhydride.

[0126] BzMA: benzyl methacrylate.

[0127] DCPMA: dicyclopentyl methacrylate.

[0128] GMA: Glycidyl methacrylate.

[0129] St: Styrene.

[0130] AIBN: azobisisobutyronitrile.

[0131] TDMAMP: tris-dimethylaminomethylphenol.

[0132] HQ: Hydroquinone.

[0133] TEA: triethylamine.

[0134] (Synthesis example 1)

[0135] BPFE (114.4 g (0.23 mol)), AA (33.2 g (0.46 mol)), PGMEA (157 g) and TEAB (0.48 g) were placed in a four-necked flask (500 ml capacity) with a reflux cooler, and stirred at 100°C to 105°C for 20 hours to react. Then, BPDA (35.3 g (0.12 mol)) and THPA (18.3 g (0.12 mol)) were added to the reaction product in the flask, and stirred at 120°C to 125°C for 6 hours to obtain a resin solution containing a photocurable cardo resin. The solid content concentration of this resin solution was 56.1% by mass, the acid value (solid content conversion) was 103 mgKOH / g, and the Mw according to GPC analysis was 3600.

[0136] (Synthesis example 2)

[0137] PGMEA (300 g) was placed in a four-necked flask (1 L capacity) with a reflux cooler, and the gas phase in the flask was replaced with nitrogen, and then the temperature was raised to 120° C. A monomer mixture (a mixed solution prepared by dissolving AIBN (10 g) in a liquid mixture of BzMA (35.2 g (0.20 mol)), DCPMA (77.1 g (0.35 mol)), GMA (49.8 g (0.35 mol)) and St (10.4 g (0.10 mol))) was added dropwise to the flask from a dropping funnel over 2 hours, and then stirred at 120° C. for 2 hours to obtain a copolymer solution.

[0138] Next, the gas phase in the flask system was replaced with air, and then AA (24.0 g (95% of glycidyl groups)), TDMAMP (0.8 g) and HQ (0.15 g) were added to the copolymer solution in the flask, and stirred at 120° C. for 6 hours to obtain a copolymer solution containing a polymerizable unsaturated group.

[0139] Then, THPA (45.7 g (90% of the molar number of AA added)) and TEA (0.5 g) were added to the copolymer solution containing polymerizable unsaturated groups, and the mixture was reacted at 120° C. for 4 hours to obtain a resin solution containing a photocurable acrylic resin. The solid content concentration of the resin solution was 46% by mass, the acid value (solid content conversion) was 68 mgKOH / g, and the Mw according to GPC analysis was 7900.

[0140] In addition, other components used in Examples and Comparative Examples are shown below.

[0141] (Thermosetting transparent resin)

[0142] Epoxy resin: 1,2-epoxy-4-(2-oxacyclopropyl)cyclohexane adduct of 2,2-bis(hydroxymethyl)-1-butanol ("EHPE3150" manufactured by Daicel Corporation Organic Chemical Products Company).

[0143] (Photopolymerizable monomer)

[0144] DPHA: A mixture of dipentaerythritol hexaacrylate and dipentaerythritol pentaacrylate ("DPHA" manufactured by Nippon Kayaku Co., Ltd.).

[0145] (Hardener)

[0146] TMA: trimellitic acid.

[0147] (Polymerization initiator)

[0148] OXE02: ethyl ketone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyl oxime) ("Irgacure OXE02" manufactured by BASF Japan Ltd.).

[0149] (Inorganic filler)

[0150] Silica A: fumed silica (“Aerosil” manufactured by Japan Aerosil Co., Ltd.), refractive index: 1.46, average particle size (distribution measurement: dynamic light scattering method, distribution analysis: cumulant method): 170 nm.

[0151] Silica B: organic silica sol ("PMA-ST" manufactured by Nissan Chemical Co., Ltd.), refractive index: 1.46, average particle size (distribution measurement: dynamic light scattering method, distribution analysis: cumulant method): 20 nm.

[0152] (Light-shielding ingredient)

[0153] Carbon black: Carbon black ("MA14" manufactured by Mitsubishi Chemical Corporation), average particle size (distribution measurement: dynamic light scattering method, distribution analysis: cumulant method): 150 nm.

[0154] (Organic solvent)

[0155] PGMEA: propylene glycol monomethyl ether acetate.

[0156] (Example 1)

[0157] First, the resin solution containing the photocurable cardol resin obtained in Synthesis Example 1, silica A, and PGMEA were mixed so that the contents of the components were as shown in Table 1 to prepare a resin composition solution for an antireflection layer. Furthermore, the resin solution containing the photocurable cardol resin obtained in Synthesis Example 1, DPHA, carbon black, OXE02, and PGMEA were mixed so that the contents of the components were as shown in Table 1 to prepare a resin composition solution for a light shielding layer.

[0158] Next, the anti-reflection layer resin composition solution was applied to the glass substrate using a spin coater and heated (prebaked) at 90° C. for 1 minute using a hot plate to form an anti-reflection layer resin composition layer having an average thickness of 80 nm. The surface roughness of the anti-reflection layer resin composition layer was 75 nm.

[0159] On the antireflection layer resin composition layer, the light-shielding layer resin composition solution was applied using a spin coater and heated (prebaked) at 90° C. for 1 minute using a hot plate to form a light-shielding layer resin composition layer.

[0160] On the laminated coating film including the antireflection layer resin composition layer and the light-shielding layer resin composition layer thus formed, an exposure gap was adjusted to 100 μm, and a mask for forming a light-shielding film pattern with a line width (line) / space (space) = 20 μm / 20 μm was used, and an i-ray intensity of 30 mW / cm 2 Ultra-high pressure mercury lamp, irradiation 50mJ / cm 2 The exposed laminated coating was exposed to ultraviolet light to cure the resin in the photosensitive part. A 0.04% potassium hydroxide aqueous solution was used at 24°C and 1 kgf / cm 2 The spray development was started under the condition of 5kgf / cm2. After the pattern began to appear, the spray development was continued for 20 seconds. 2The unexposed part of the laminated coating was removed by spraying water under pressure, and a light-shielding film pattern in which an anti-reflection layer pattern and a light-shielding layer pattern were sequentially stacked was formed on the glass substrate. Thereafter, the light-shielding film pattern was subjected to a heat treatment (post-baking) at 230° C. for 30 minutes using a hot air dryer. In addition, the average thickness of the light-shielding layer pattern was 1.3 μm.

[0161] (Example 2 to Example 3)

[0162] In the anti-reflection layer resin composition solution, the resin solution of the photocurable cardol resin obtained in Synthesis Example 1 and the amount of silica A were changed so that each component had the content shown in Table 1. A light-shielding film pattern in which an anti-reflection layer pattern and a light-shielding layer pattern were sequentially laminated was formed on a glass substrate in the same manner as in Example 1. The surface roughness of the anti-reflection layer resin composition layer obtained in Example 2 was 98 nm, and the surface roughness of the anti-reflection layer resin composition layer obtained in Example 3 was 142 nm.

[0163] (Example 4)

[0164] In addition to forming an antireflection layer resin composition layer with an average thickness of 40 nm, a light-shielding film pattern in which an antireflection layer pattern and a light-shielding layer pattern were sequentially stacked was formed on a glass substrate in the same manner as in Example 3. In addition, the surface roughness of the antireflection layer resin composition layer obtained in Example 4 was 150 nm.

[0165] (Example 5)

[0166] In addition to forming an antireflection layer resin composition layer with an average thickness of 200 nm, a light-shielding film pattern in which an antireflection layer pattern and a light-shielding layer pattern were sequentially stacked was formed on a glass substrate in the same manner as in Example 3. In addition, the surface roughness of the antireflection layer resin composition layer obtained in Example 5 was 50 nm.

[0167] (Example 6)

[0168] In the anti-reflection layer resin composition solution, a light-shielding film pattern in which an anti-reflection layer pattern and a light-shielding layer pattern were sequentially stacked was formed on a glass substrate in the same manner as in Example 3, except that the resin solution of the photocurable acrylic resin obtained in Synthesis Example 2 was used instead of the resin solution of the photocurable cardo resin obtained in Synthesis Example 1. The surface roughness of the anti-reflection layer resin composition layer obtained in Example 6 was 131 nm.

[0169] (Example 7)

[0170] First, the resin solution of the photocurable cardol resin obtained in Synthesis Example 1, epoxy resin, TMA, silica A and PGMEA were mixed so that the components had the contents shown in Table 1 to prepare a resin composition solution for an antireflection layer. Then, a resin composition solution for a light shielding layer was prepared in the same manner as in Example 1.

[0171] Next, the antireflection layer resin composition solution was applied to the glass substrate using a spin coater, and then heat-cured at 230° C. for 30 minutes using a hot air dryer to form an antireflection layer with an average thickness of 80 nm. The surface roughness of this antireflection layer was 65 nm.

[0172] The light-shielding layer resin composition solution was applied on the antireflection layer using a spin coater and heated (prebaked) at 90° C. for 1 minute using a hot plate to form a light-shielding layer resin composition layer.

[0173] On the light-shielding layer resin composition layer thus formed, an exposure gap was adjusted to 100 μm, and a light-shielding film pattern formation mask with a line width / space of 20 μm / 20 μm was applied. 2 Ultra-high pressure mercury lamp, irradiation 50mJ / cm 2 The exposed light-shielding layer resin composition layer was exposed to ultraviolet light to photoharden the resin in the photosensitive portion. A 0.04% potassium hydroxide aqueous solution was used at 24°C and 1 kgf / cm 2 The spray development was started under the condition of 5kgf / cm2. After the pattern began to appear, the spray development was continued for 20 seconds. 2 The unexposed part of the light-shielding layer resin composition layer was removed by spraying water under pressure, and a light-shielding film pattern with an anti-reflection layer and a light-shielding layer pattern stacked in sequence was formed on the glass substrate. Thereafter, the light-shielding film pattern was subjected to a heat treatment (post-baking) at 230° C. for 30 minutes using a hot air dryer. In addition, the average thickness of the light-shielding layer pattern was 1.3 μm.

[0174] (Example 8)

[0175] In the anti-reflection layer resin composition solution, epoxy resin, TMA, silica A and PGMEA were mixed so that each component had the content shown in Table 1, and a light-shielding film pattern in which an anti-reflection layer and a light-shielding layer pattern were sequentially laminated was formed on a glass substrate in the same manner as in Example 7. The surface roughness of the anti-reflection layer obtained in Example 8 was 70 nm.

[0176] (Comparative Example 1)

[0177] A light-shielding film pattern including only a light-shielding layer pattern was formed on a glass substrate in the same manner as in Example 1 except that the antireflection layer was not formed.

[0178] (Comparative Example 2)

[0179] In the anti-reflection layer resin composition solution, the resin solution of the photocurable cardo resin obtained in Synthesis Example 1 and PGMEA were mixed so that each component had the content shown in Table 1, and a light-shielding film pattern in which an anti-reflection layer pattern and a light-shielding layer pattern were sequentially stacked was formed on a glass substrate in the same manner as in Example 1. The surface roughness of the anti-reflection layer resin composition layer obtained in Comparative Example 2 was 11 nm.

[0180] (Comparative Example 3)

[0181] A light-shielding film pattern in which an antireflection layer pattern and a light-shielding layer pattern were sequentially stacked was formed on a glass substrate in the same manner as in Example 3, except that silicon dioxide B having an average particle size of 20 nm was used instead of silicon dioxide A having an average particle size of 170 nm. The surface roughness of the resin composition layer for an antireflection layer obtained in Comparative Example 3 was 30 nm.

[0182] <Measurement of light blocking degree (optical density (OD) value)>

[0183] The optical density (OD value) of the obtained glass substrate with a light-shielding film pattern was measured using an optical densitometer ("X-Rite361T(V)" manufactured by Sakata Ink Engineering Co., Ltd.), and the optical density (OD value) was corrected by the optical density (OD value) of the glass substrate to obtain the light-shielding degree (OD value) of the light-shielding film. The results are shown in Table 1.

[0184] <Reflectivity measurement>

[0185] The reflectance [%] was measured from the side of the obtained glass substrate with a light-shielding film pattern on which the light-shielding film pattern was not formed using a spectrophotometer ("UH4150" manufactured by Hitachi High Tech Science Co., Ltd.) under the conditions of light source C and a 2° field of view. The results are shown in Table 1.

[0186]

[0187] As shown in Table 1, it was confirmed that the shading film patterns including an anti-reflection layer formed by curing an anti-reflection layer with a specific surface roughness (Examples 1 to 6) and the shading film patterns including an anti-reflection layer with a specific surface roughness (Examples 7 to 8) had lower reflectivity than the shading film pattern without an anti-reflection layer (Comparison Example 1), the shading film pattern in which the anti-reflection layer does not contain inorganic filler (Comparison Example 2), and the shading film pattern including an anti-reflection layer formed by curing a resin composition layer for an anti-reflection layer with a small surface roughness (Comparison Example 3).

[0188] [Industrial Applicability]

[0189] As described above, according to the present invention, a light-shielding film in which reflection of light is fully suppressed can be obtained. Therefore, the display device substrate of the present invention is useful as a substrate used in display devices such as liquid crystal displays, touch screens, organic electroluminescence (EL) displays, and quantum dot displays because it has a light-shielding film in which reflection of light is fully suppressed.

Claims

1. A substrate for a display device, characterized in that: include: Transparent substrate; as well as A shading film, the shading film comprising: an anti-reflection layer disposed on the transparent substrate, containing an inorganic filler having a refractive index of 1.2 to 1.8 and an average particle size of 25 nm to 300 nm and a transparent resin hardener, and having an average thickness of 0.01 μm to 1 μm; and a shading layer disposed on the anti-reflection layer, containing at least one shading component selected from the group consisting of an organic black pigment, an inorganic black pigment and a mixed color pseudo black pigment and a resin hardener, and having an average thickness of 0.1 μm to 30 μm, wherein the average particle size of the shading component is 50 nm to 300 nm, and the surface roughness of the anti-reflection layer at the interface between the anti-reflection layer and the shading layer is 40 nm to 200 nm.

2. The display device substrate according to claim 1, wherein: The average particle size of the inorganic filler is 170nm to 300nm.

3. The display device substrate according to claim 1 or 2, characterized in that: The content of the inorganic filler is 5% by mass to 95% by mass based on the entire antireflection layer.

4. A method for manufacturing a substrate for a display device, the substrate for a display device comprising a transparent substrate and a light-shielding film including an anti-reflection layer and a light-shielding layer disposed on the transparent substrate, the method for manufacturing a substrate for a display device being characterized by comprising: A step of forming a resin composition layer for an antireflection layer on the transparent substrate, which contains an inorganic filler with a refractive index of 1.2 to 1.8 and an average particle size of 25 nm to 300 nm and a photocurable transparent resin, has an average thickness of 0.01 μm to 1 μm and a surface roughness of 40 nm to 200 nm; A step of forming a light-shielding layer resin composition layer containing at least one light-shielding component selected from the group consisting of an organic black pigment, an inorganic black pigment, and a mixed color pseudo black pigment and a photocurable resin on the anti-reflection layer resin composition layer; as well as The step of performing exposure treatment on the resin composition layer for the antireflection layer and the resin composition layer for the light-shielding layer, performing development treatment on the layer, and performing post-baking to form an antireflection layer containing the inorganic filler and the transparent resin cured product and a light-shielding layer containing the light-shielding component and the resin cured product and having an average thickness of 0.1 μm to 30 μm.

5. The method for manufacturing a display device substrate according to claim 4, wherein: The photocurable transparent resin in the antireflection layer resin composition layer and the photocurable resin in the light shielding layer resin composition layer are both alkali soluble, the development treatment is an alkali development treatment, and the average particle size of the inorganic filler is 170 nm to 300 nm.

6. A method for manufacturing a substrate for a display device, the substrate for a display device comprising a transparent substrate and a light-shielding film including an anti-reflection layer and a light-shielding layer disposed on the transparent substrate, the method for manufacturing a substrate for a display device being characterized by comprising: A step of heat-curing a resin composition for an anti-reflection layer containing an inorganic filler having a refractive index of 1.2 to 1.8 and an average particle size of 25 nm to 300 nm and at least one of a thermosetting transparent resin and a thermosetting monomer on the transparent substrate to form an anti-reflection layer having an average thickness of 0.01 μm to 1 μm and a surface roughness of 40 nm to 200 nm; and On the anti-reflection layer, a light-shielding layer resin composition containing at least one light-shielding component selected from the group consisting of organic black pigment, inorganic black pigment and mixed-color pseudo-black pigment and a photocurable resin is subjected to exposure treatment, development treatment, and post-baking to form a light-shielding layer with an average thickness of 0.1μm to 30μm.

7. The method for manufacturing a display device substrate according to claim 6, wherein: The photocurable resin in the light-shielding layer resin composition is alkali-soluble, the development treatment is an alkali development treatment, and the average particle size of the inorganic filler is 170 nm to 300 nm.

8. A resin composition solution for an antireflection layer, which is used in the method for manufacturing a display device substrate according to claim 5, and is a resin composition solution containing a photocurable resin composition and an organic solvent capable of forming a resin composition layer for an antireflection layer having an average thickness of 0.01 μm to 1 μm and a surface roughness of 40 nm to 200 nm, and characterized in that: The photocurable resin composition contains: 5% to 95% by mass of an inorganic filler having a refractive index of 1.2 to 1.8 and an average particle size of 170 nm to 300 nm and being dispersible in the organic solvent relative to the entire resin composition; 1.54% to 95% by mass of a photocurable transparent resin relative to the entire resin composition; 0% to 50% by mass of a photopolymerizable monomer relative to the total amount of the photocurable transparent resin and the photopolymerizable monomer; and 0% to 30% by mass of a photopolymerization initiator relative to 100 parts by mass of the total amount of the photocurable transparent resin and the photopolymerizable monomer, and The content of the organic solvent is 80 mass % to 99.9 mass % relative to the total amount of the photocurable resin composition and the organic solvent. The solution viscosity is 1 mPa·sec~4 mPa·sec.

9. A resin composition solution for an antireflection layer, which is used in the method for manufacturing a display device substrate according to claim 7, and is a resin composition solution containing a thermosetting resin composition capable of forming an antireflection layer having an average thickness of 0.01 μm to 1 μm and a surface roughness of 40 nm to 200 nm and an organic solvent, and is characterized in that: The thermosetting resin composition comprises: 5% to 95% by mass of an inorganic filler having a refractive index of 1.2 to 1.8 and an average particle size of 170 nm to 300 nm and dispersible in the organic solvent relative to the entire resin composition; 3.2% to 94.06% by mass of at least one of a thermosetting transparent resin and a thermosetting monomer relative to the entire resin composition; and 1 part to 25 parts by mass of a thermosetting agent relative to 100 parts by mass of the total amount of the thermosetting transparent resin and the thermosetting monomer, and The content of the organic solvent is 80% by mass to 99.9% by mass relative to the total amount of the resin composition for an antireflection layer and the organic solvent. The solution viscosity is 1 mPa·sec~4 mPa·sec.

Citation Information

Patent Citations

  • Black resin composition for light blocking films, substrate with light blocking film obtained by curing composition, color filter having substrate with light blocking film, and touch panel

    JP2016161926A

  • Photosensitive resin composition for light-shielding film having spacer function, light-shielding film, liquid crystal display device, production method of photosensitive resin composition for light-shielding film having spacer function, production method of light-shielding film, and method for manufacturing liquid crystal display device

    JP2017072760A

  • Photosensitive resin composition for light-shielding film, substrate for display including light-shielding film formed by curing the photosensitive resin composition, and method for manufacturing substrate for display

    JP2017181976A

  • Substrate, and display panel provided with substrate

    WO2010070929A1

  • Substrate for display devices, method for producing substrate for display devices, and display device

    WO2014178149A1